2018
DOI: 10.1111/hojo.12304
|View full text |Cite
|
Sign up to set email alerts
|

Progression from Cafeteria toà la carteOffending: Scottish Organised Crime Narratives

Abstract: This article presents insights from qualitative research into organised crime (OC) in Glasgow, Scotland. Interviews were conducted with a sample of 42 current and former offenders with a history of group offending in an attempt to understand variation in the onset, maintenance, and cessation of OC careers. Offending narratives revealed different OC trajectories. Drug dealing was the primary modus operandi of OC groups, but some offenders exhibited versatility and progression to wider criminal activity or a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For example, the violence of organised crime groups tends to be policed separately from gang violence, but in practice, some gangs evolve and gang members can be embedded within organised crime networks (Densley, 2014;Densley et al, 2019;McLean and Densley, 2020;Roks and Densley, 2020). Gang members also fulfil a number of non-violent and noncriminal roles (Fraser and Atkinson, 2014), many gang members go out of their way to avoid violence (Garot, 2010), and a fear of retaliation is often a much more important driver of conflict than the will to violence itself (Vandenbogaerde and Van Hellemont, 2016).…”
Section: Policing the "Criminologists" Gangmentioning
confidence: 99%
“…For example, the violence of organised crime groups tends to be policed separately from gang violence, but in practice, some gangs evolve and gang members can be embedded within organised crime networks (Densley, 2014;Densley et al, 2019;McLean and Densley, 2020;Roks and Densley, 2020). Gang members also fulfil a number of non-violent and noncriminal roles (Fraser and Atkinson, 2014), many gang members go out of their way to avoid violence (Garot, 2010), and a fear of retaliation is often a much more important driver of conflict than the will to violence itself (Vandenbogaerde and Van Hellemont, 2016).…”
Section: Policing the "Criminologists" Gangmentioning
confidence: 99%
“…British criminologists have often struggled with and contested the concept of the gang, focusing instead on youth formations and subcultures. However, building on earlier findings (Pitts, 2008), recent research has indicated that not only is the existence of street gangs a reality in many UK cities, but that gang life is evolving in some contexts (Densley, 2014;Densley et al, 2018;McLean, 2017). Densley (2014, p.22) highlights that recreation, crime, enterprise and governance represent 'actualization stages through which gangs progress' in London, and alludes to similar evolution processes emerging in cities like Manchester.…”
Section: Introductionmentioning
confidence: 99%